2017
DOI: 10.5267/j.ijiec.2016.9.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of optimization techniques for MRR and surface roughness in wire EDM process for gear cutting

Abstract: The objective of the present work is to use a suitable method that can optimize the process parameters like pulse on time (TON), pulse off time (TOFF), wire feed rate (WF), wire tension (WT) and servo voltage (SV) to attain the maximum value of MRR and minimum value of surface roughness during the production of a fine pitch spur gear made of copper. The spur gear has a pressure angle of 20⁰ and pitch circle diameter of 70 mm. The wire has a diameter of 0.25 mm and is made of brass. Experiments were conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The standard orthogonal array (OA) L12 (2 4 ) was selected for the current study after two levels and four factors of degrees of freedom (DOFs) were analyzed [15,16]. Table 3 illustrates how its twelve rows correlate with the number of experiments or assessments.…”
Section: Design Of Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard orthogonal array (OA) L12 (2 4 ) was selected for the current study after two levels and four factors of degrees of freedom (DOFs) were analyzed [15,16]. Table 3 illustrates how its twelve rows correlate with the number of experiments or assessments.…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…Thus, in order to appropriately assign values to various responses under optimization, a fair criterion for the objective calculation of weight factors must be developed [16].…”
Section: Multi-criteria Cutting Parameter Optimization Analysismentioning
confidence: 99%
“…Besides, many other methods have also been used as Artificial neural network, Response surface methodology, and Taguchi's combination with other methods (GRA, MOORA-PCA, VIKOR, multiple response signal-to-noise, weighted signal-to-noise,...) for multi-target optimization in EDM (Tirumala et al, 2018;Munmun & Kalipad, 2017;Bhaumik & Maity, 2017;Nayaka et al, 2017;Munmun & Kalipada, 2017;Dey & Chakraborty, 2015). However, Taguchi-TOPSIS and Taguchi-GRA are the most commonly used (Kumar et al, 2018;Zerti et al, 2018;Mohapatraa et al, 2017). Dastagiri et al (2016) have shown that TOPSIS-Taguchi is more effective than Taguchi-GRA in multi-response optimization of PMEDM.…”
Section: Introductionmentioning
confidence: 99%
“…The results proved that the optimum combination was found through the use of different methods. Mohapatraa et al (2017) used two multi objective optimization methods for MRR and surface quality comparison of optimization techniques for MRR and surface roughness in the wire EDM process for gear cutting. He investigated the comparison of the wire EDM phenomenon using the Taguchi quality loss function and the hybrid optimization method.…”
Section: Introductionmentioning
confidence: 99%